Practising Piety : Spiritual Intermediality and Devotion in Early Modern Europe - Dirschauer, Marlene,; Föcking, Marc,; Gerrits, Rogier,; Ryrie, Alec, (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
Situated at the intersection of theology, history, literature, and the arts, this edited volume introduces the concept of spiritual intermediality and highlights its central role in early modern piety across various Christian denominations. The case studies present a diverse array of perspectives that explore different forms and functions of intermediality in devotional practices of 16th- and 17th-century Europe, thereby enhancing our understanding of the medial conditions and intermedial aspects of devotion during one of the most fruitful periods of devotional arts and practices in Europe. By arguing that early modern devotion often relied on intermedial forms of expression to unfold its full semantic and performative potential, the volume sheds new light on the rich web of media that shaped early modern Christian culture. Contributors include: Wietse de Boer, Marlene Dirschauer, Marc Föcking, Rogier Gerrits, Tara Hamling, Jenny Körber, Judith Lipperheide, Cosima Macco, Alec Ryrie, Franziska Schreiber, James Simpson, Jeffrey Chipps Smith, Stephanie Wodianka, and Katharina Worms.